2011
DOI: 10.1099/mic.0.052506-0
|View full text |Cite
|
Sign up to set email alerts
|

HXK1 regulates carbon catabolism, sporulation, fumonisin B1 production and pathogenesis in Fusarium verticillioides

Abstract: In Fusarium verticillioides, a ubiquitous pathogen of maize, virulence and mycotoxigenesis are regulated in response to the types and amounts of carbohydrates present in maize kernels. In this study, we investigated the role of a putative hexokinase-encoding gene (HXK1) in growth, development and pathogenesis. A deletion mutant (Dhxk1) of HXK1 was not able to grow when supplied with fructose as the sole carbon source, and growth was impaired when glucose, sucrose or maltotriose was provided. Additionally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 54 publications
3
31
0
Order By: Relevance
“…Conidiation-related genes may therefore be linked to some extent with pathogenicity-related genes. This hypothesis is further supported by the results of various other studies on plant fungi (Yi et al, 2008;Kim et al, 2011). In the present study, no relationship was observed between the colony color and the pathogenicity of the isolates.…”
Section: Discussionsupporting
confidence: 88%
“…Conidiation-related genes may therefore be linked to some extent with pathogenicity-related genes. This hypothesis is further supported by the results of various other studies on plant fungi (Yi et al, 2008;Kim et al, 2011). In the present study, no relationship was observed between the colony color and the pathogenicity of the isolates.…”
Section: Discussionsupporting
confidence: 88%
“…For purification, FB1 crude extracts were passed through equilibrated HyperSep C18 SPE columns (Thermo Fisher Scientific) and ergosterol crude extracts were passed over Acrodisc 13 mm nylon 0.45 mm filters (Pall Life Sciences). HPLC analyses of FB1 and ergosterol were performed as described elsewhere (Shim & Woloshuk, 1999;Kim et al, 2011). FB1 levels were then normalized to ergosterol contents.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the genes encoding hexokinase (HXK1 and −2), aminotransferase (ALT2 and SER1) and the citrate transporter (CTP1) are positive knockouts for improving isoprenoid fluxes. HXK1 and −2 are isoenzymes acting on glucose metabolism in the upper glycolytic pathway [36], [37]. It was reported that deletion of HXK2 led to a 10-fold increase of HXK1 expression in S. cerevisiae strains [38].…”
Section: Discussionmentioning
confidence: 99%